Molecular Mechanisms of Plant and Microbe Coexistence - Nautiyal, Chandra Shekhar; Dion, Patrice (Soil Biology, 2008)
Molecular Mechanisms of Plant and Microbe Coexistence presents studies on the complex and manifold interactions of plants and microbes at the population, genomics and proteomics level. The role of soil microbial diversity in enhancing plant health and plant microbe beneficial symbioses is discussed. Microbial communities are shown in the light of evolution. Main topics include genome coexistence and the functional genomics and proteomics of plant-associated microbes, which could form the basis for new environmentally benign strategies to combat infectious plant diseases and regulate plant growth. Further chapters focus on the role of signaling during the different stages of plant microbe coexistence, in symbiotic or pathogenic relationships, in quorum sensing and plant viral infections. Methods for studying the interactions in the root zone complement the book, which will certainly be of relevance in the practical application to agriculture, food security and for maintaining the balance of our ecosystems.